2017
DOI: 10.18203/issn.2454-5929.ijohns20174349
|View full text |Cite
|
Sign up to set email alerts
|

Sphenochoanal polyp: a case report

Abstract: <p class="abstract">Choanal polyp arising from the sphenoid sinus and presenting at the choana are rare. These are known as sphenochoanal polyp. We present a case of sphenochoanal polyp and its clinical features and surgical management is discussed. Our aim in this case was to properly delineate the origin of the polyp and differentiate it from other lesions such as the antrochoanal polyp and meningocele, followed by meticulous endoscopic excision of the polyp. Radiological investigations include a CT sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…3,6 Some researchers also suggest early exploration when CSF rhinorrhea is encountered in the presence of trauma. 25,26 The outcome of this study is closely similar to the reports of some earlier researchers. The variations in the treatments used to arrest the CSF leak might be due to the type, severity of the injuries or the size of the skull base defects which suggest that as the injuries or defects become more severe, the protocol tends toward surgical intervention.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…3,6 Some researchers also suggest early exploration when CSF rhinorrhea is encountered in the presence of trauma. 25,26 The outcome of this study is closely similar to the reports of some earlier researchers. The variations in the treatments used to arrest the CSF leak might be due to the type, severity of the injuries or the size of the skull base defects which suggest that as the injuries or defects become more severe, the protocol tends toward surgical intervention.…”
Section: Discussionsupporting
confidence: 89%
“…Though, the period of follow-up in this study may be regarded as short as complication has been reported decades after the initial traumatic craniofacial injury. 26 In addition, the presence of craniocerebral injuries sometimes leads to delays in treatment of maxillofacial fractures and may actually increase the risk of complication. 25,26 Clinical evidence shows that the longer a CSF leak persists, the greater the risk of meningitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This also helps better visualization of the sinus intraoperatively. 8 Recurrence can be prevented by complete removal of the polyp. Regular follow-up is essential.…”
Section: Discussionmentioning
confidence: 99%